FRI0211 Safety and efficacy of subcutaneous golimumab in chinese patients with active rheumatoid arthritis despite mtx therapy: results from a randomized, placebo-controlled, phase 3 trial. (23rd January 2014) - Li, Z.; Zhang, F.; Kay, J.; Fei, K.; Han, C.; Zhuang, Y.; Wu, Z.; Hsia, E. C.
Abstract : Objectives: Assess safety and efficacy of GLM+MTX over 1yr in a multicenter, randomized, placebo (PBO)-controlled study of Chinese pts with active RA despite MTX therapy. Methods: 264 pts were randomized (1:1) to subcutaneous PBO+MTX (Group1) or GLM 50mg+MTX (Group2) q4wks. All pts received stable doses of oral MTX (7.5-20mg/wk). Group1 pts with inadequate treatment response entered blinded early escape to GLM 50mg+MTX at wk16. All remaining Group1 pts switched to GLM 50mg+MTX at wk24. Blinding to randomization assignment was maintained through wk 56. The last GLM injection was at wk48; the last efficacy assessment was wk52. The primary endpoint was ACR20 at wk14. Efficacy assessments included DAS28-CRP, HAQ-DI, SF-36 PCS and MCS, and FACIT-Fatigue scores. Adverse events (AEs) were monitored through wk56. Results: Baseline demographics and disease characteristics were generally similar between the groups; median age was 49 yrs and 81.1% of pts were female. 23 (8.7%) pts discontinued treatment through wk56. Efficacy results are shown in the table . At wk14, 15.9% of Group1 pts and 40.9% of Group2 pts had ACR20 response (p<0.001). At wk24, Group2 pts had significantly greater improvements in DAS28-CRP, SF-36 PCS and MCS scores, and FACIT-fatigue score. A greater proportion of Group2 pts had HAQ-DI improvement ≥0.25 vs. Group1. The responses to GLM+MTX therapy were maintained through wk52 in Group2; after switching to GLM, Group1 pts also achieved rapid improvement. Through wk16, 23.5% of Group1 pts and 26.7% of Group2 pts reported AEs (infections were the most common); 0.8% and 1.5% reported serious AEs. Through wk56, 130/259 (50.2%) of GLM+MTX-treated pts had an AE, and 11/259 (4.2%) had an SAE. 3 serious infections (pneumonia, lung infection, respiratory tract infection) and 1 death (acute myocardial infarction) occurred in GLM+MTX-treated pts. No malignancies or opportunistic infections were reported. Only 1 pt had an injection site reaction (mild pain). Of the 251 GLM+MTX-treated pts with available samples, 6 (2.4%) were positive for antibodies to GLM through wk52. Conclusions: Among Chinese pts with RA, GLM+MTX-treated pts had significantly greater improvements in RA signs/symptoms vs. PBO+MTX-treated pts through wk24, and responses were maintained through wk52. GLM+MTX was well tolerated and no unexpected safety events occurred through wk56. In Chinese pts, GLM+MTX demonstrated efficacy and acceptable safety similar to that in a global population in the GO-FORWARD trial. Disclosure of Interest : Z. Li Grant/research support from: Janssen R&D, LLC, F. Zhang Grant/research support from: Janssen R&D, LLC, J. Kay Grant/research support from: Janssen R&D, LLC, K. Fei Shareholder of: Johnson & Johnson, Employee of: Janssen R&D, LLC, C. Han Shareholder of: Johnson & Johnson, Employee of: Janssen R&D, LLC, Y. Zhuang Shareholder of: Johnson & Johnson, Employee of: Janssen R&D, LLC, Z. Wu Shareholder of: Johnson & Johnson, Employee of: Janssen R&D, LLC, E. Hsia Shareholder of: Johnson & Johnson, Employee of: Janssen R&D, LLC